2005
DOI: 10.1111/j.1471-8286.2005.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐amplification of polymorphic microsatellites reveals extra‐pair paternity and brood parasitism in Sturnus vulgaris

Abstract: We tested the cross-amplification of 37 microsatellites in a population of starlings ( Sturnus vulgaris ). Twenty-three of them amplified and five exhibited a large number of alleles per locus and high heterozygosity (on average: 14.6 alleles / locus and H E = 0.704). We assessed the occurrence of extra-pair paternity (EPP) and intraspecific brood parasitism (IBP) in this population. The EPP rate was 16 % to 18% offspring from 43% to 45% of nests. IBP was very variable between two successive years (14% to 27% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
(8 reference statements)
1
7
0
Order By: Relevance
“…The results of parentage analyses show no evidence for extra‐pair paternity (EPP) or intra‐specific brood parasitism (IBP). While rates of IBP and EPP in natural populations reported in the literature vary, these are generally relatively low (EPP: 9–17% of offspring and 29–45% of nests; IBP: 0–27% of chicks and 0–45% of nests) and it has been suggested that these may reflect local ecological conditions (Loyau et al 2005). Thus, it is possible that the reduced space and increased food availability lowered the energetic costs of nest and mate guarding leading to the absence of EPP and IBP, at least in the nests that were examined.…”
Section: Discussionmentioning
confidence: 99%
“…The results of parentage analyses show no evidence for extra‐pair paternity (EPP) or intra‐specific brood parasitism (IBP). While rates of IBP and EPP in natural populations reported in the literature vary, these are generally relatively low (EPP: 9–17% of offspring and 29–45% of nests; IBP: 0–27% of chicks and 0–45% of nests) and it has been suggested that these may reflect local ecological conditions (Loyau et al 2005). Thus, it is possible that the reduced space and increased food availability lowered the energetic costs of nest and mate guarding leading to the absence of EPP and IBP, at least in the nests that were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although high levels of both intraspecific nest parasitism and extra‐pair paternity occur in both species (Cordero et al . 2003; Loyau et al . 2005), no microsatellite markers have been developed specifically for them.…”
Section: Characteristics Of Sturnus Unicolor Microsatellite Loci Tamentioning
confidence: 99%
“…2003). Recently, Loyau et al . (2005) used five microsatellites developed for other species to evaluate extra‐pair paternity and intraspecific nest parasitism in European starlings.…”
Section: Characteristics Of Sturnus Unicolor Microsatellite Loci Tamentioning
confidence: 99%
See 1 more Smart Citation
“…Each 10 µL PCR contained: 0.5–1 U JumpStart™ Taq DNA polymerase (Sigma), 0.2 m m dNTPs (Invitrogen), 10 m m Tris‐HCL (pH 8.3), 50 m m KCl, 1–3 m m MgCl 2 , 0.15 µ m of forward and reverse primers and 1–50 ng of genomic DNA. PCRs consisted of 35 cycles at 94 °C for 50 s, T a for 1 min, 72 °C for 1 min and a final extension at 72 °C for 4 min 30 s. I also tested six markers — four of which were polymorphic in the European starling (Loyau et al . 2005) — developed for other passerine species using the same methods ().…”
Section: Characterization Of 31 Polymorphic Microsatellite Loci From mentioning
confidence: 99%